Translating Yemeni cartoons into English: A Systemic Functional Linguistics approach - Al-Kenani, Tawffeek Abdou Saeed Mohammed; Banda, Felix (Stellenbosch Papers in Linguistics Plus, 2018)
This study deals with the problems involving translating Arabic cartoons into English and the strategies that can be adopted by a translator to make them more accessible and more target-audience friendly. It uses an approach based on Halliday’s Systemic Functional Linguistics (SFL; Halliday 1985/1994; Halliday and Matthiessen 2004). The concept of equivalence is revisited within the framework of SFL to include register analysis and the three strands of meaning or metafunctions. The study is based on a number of Yemeni cartoons that have been translated in the Yemen Times, a prominent English-language Yemeni newspaper. The study concludes that if a cartoon is to be translated in such a way that the target cartoon sounds as natural and entertaining to the target audience as the original, the translator should take into account the context of culture, the context of situation (i.e., register analysis) and the metafunction(s) involved in the source cartoon and tries to render them as far as possible in the target language. In addition, a cartoon is a multi-semiotic genre in which both text and image go hand in hand. The image-text semantic relation in this multi-model discourse can facilitate the comprehension of the context and the interpretation of the schemata of the cartoons more clearly. The translation of a cartoon cannot be achieved unless the two codes are considered.